Community Empowerment Through Making Snacks as a Home-Scale Business to Improve Community Welfare During the Pandemic in Cipeujeuh Kulon Village - Siti Rokhmah; Siti Julaekha; Romlah; Yuni Tazkiyah; Siti Marwah; Tati Haryati; Dahlia Arum Wangi; Navila Amalia; Taib Maulana; Nanang Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Community Service Lecture (KPM) aims to carry out the tridharma function of higher education for every IAI Bunga Bangsa Cirebon Lecturer. One of the tridharma is carrying out community service by